2020
DOI: 10.1016/j.iref.2020.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Does the risk on banks’ balance sheets predict banking crises? New evidence for developing countries

Abstract: Simulation results of our theoretical model for banks' risk-taking behavior suggest that during booms banks have high non-core liabilities, high leverage and few liquid assets, while the reverse holds during busts. We investigate the predictive power of these bank balance sheet variables for future banking crises using monthly data of 147 developing countries for the period 1980-2016. Our results suggest that low levels of liquid assets and domestic financial liabilities, high levels of foreign liabilities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
(51 reference statements)
1
4
0
Order By: Relevance
“…In the banking literature, the variables that reflect bank fundamentals are CAMEL variables, which relate to management, capital adequacy, efficiency, management, and earnings. Indeed, a comprehensive set of recent studies confirmed the early findings that these indicators are good predictors of bank failure (Liu et al, 2021;De Haan et al, 2020;Bongini et al, 2018). Accordingly, we suggest our second hypothesis: Hypothesis 2: BETA depends significantly on the CAMEL variables.…”
Section: Literature Review and Hypotheses Developmentsupporting
confidence: 78%
“…In the banking literature, the variables that reflect bank fundamentals are CAMEL variables, which relate to management, capital adequacy, efficiency, management, and earnings. Indeed, a comprehensive set of recent studies confirmed the early findings that these indicators are good predictors of bank failure (Liu et al, 2021;De Haan et al, 2020;Bongini et al, 2018). Accordingly, we suggest our second hypothesis: Hypothesis 2: BETA depends significantly on the CAMEL variables.…”
Section: Literature Review and Hypotheses Developmentsupporting
confidence: 78%
“…To identify the effect of macroeconomic conditions, the commonly used macroeconomic variables are the annual percent change of the GDP and the annual percent change of inflation. Thus, based on previous studies in this area it can be concluded that economic growth (GDP) has a positive effect on a bank's performance (Kosmidou et al, 2005;Pasiouras and Kosmidou, 2007;Athanasoglou et al, 2008;Anbar and Alper, 2011;Derbali, 2011;Lainà et al, 2015;Shijaku, 2016;Pedro et al, 2018;de Haan et al, 2020). On the other hand, the impact of inflation on a bank's performance has been divided into two aspects: a positive relationship (Kosmidou et al, 2005;Athanasoglou et al, 2006;Pasiouras and Kosmidou, 2007;Athanasoglou et al, 2008;Pedro et al, 2018) or a negative relationship (Kosmidou, 2008;de Haan et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, based on previous studies in this area it can be concluded that economic growth (GDP) has a positive effect on a bank's performance (Kosmidou et al, 2005;Pasiouras and Kosmidou, 2007;Athanasoglou et al, 2008;Anbar and Alper, 2011;Derbali, 2011;Lainà et al, 2015;Shijaku, 2016;Pedro et al, 2018;de Haan et al, 2020). On the other hand, the impact of inflation on a bank's performance has been divided into two aspects: a positive relationship (Kosmidou et al, 2005;Athanasoglou et al, 2006;Pasiouras and Kosmidou, 2007;Athanasoglou et al, 2008;Pedro et al, 2018) or a negative relationship (Kosmidou, 2008;de Haan et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Petropoulos et al (2020) identified random forests as superior in out-of-sample and out-oftime predictive performance among US-based banks. Shrivastav and Ramudu (2020) achieved 93 percent accuracy in predicting Indian bank defaults using support vector machine methodology on a dataset spanning 2000 to 2017. de Haan et al (2020) emphasized the role of bank balance sheet information in predicting future banking crises, highlighting the significance of low bank liquid assets and high financial leverage. Filippopoulou et al (2020) evaluated risk indicators from the European Central Bank and European Systemic Risk Board, emphasizing the importance of specific banking variables over macroeconomic variables.…”
Section: Literature Reviewmentioning
confidence: 99%